2022
DOI: 10.1002/cam4.4684
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of genetic counseling and testing in a clinic‐based population of women with breast cancer

Abstract: Background The study was conducted to evaluate racial differences in referral and uptake of genetic counseling (GC) in a clinic‐based population of women with breast cancer. Methods Medical records of 150 breast cancer patients at the Karmanos Cancer Institute were reviewed to determine eligibility for GC according to National Comprehensive Cancer Network guidelines, GC referral rates, and appointment completion rates. Logistic regression was used to assess the relationship between demographic and clinical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Patients were asked to report all primary cancer types, date of cancer diagnosis, treatment received, and genetic testing status. The PHQ-4 was used to measure anxiety and depression; respondents scores were dichotomized by either none (0-2) or mild to severe (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). 25 As part of the survey, participants were asked if they had undergone cancer genetic testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were asked to report all primary cancer types, date of cancer diagnosis, treatment received, and genetic testing status. The PHQ-4 was used to measure anxiety and depression; respondents scores were dichotomized by either none (0-2) or mild to severe (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). 25 As part of the survey, participants were asked if they had undergone cancer genetic testing.…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 Another study found that among women with breast cancer who qualify for genetic testing per NCCN guidelines, only about 60% were referred and about 46% completed testing indicating that despite a referral, there is still a reduction of uptake in germline testing. 5 Patients at risk for Lynch Syndrome diagnosed with either colorectal or endometrial cancer have even lower levels of testing with one study reporting a rate around 6% and another study reporting a rate around 3%. 6 , 7 Germline genetic testing for patients with cancer can have significant impact on their cancer treatment and surveillance as well as implications for family members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, numerous barriers to genetic counseling and testing have been described. For example, publicly insured patients are less likely to undergo genetic counseling than those with private insurance [56]. Similarly, lower rates of genetic testing have been reported among racial and ethnic minorities, including Black women, who are significantly more likely to be diagnosed with early onset breast cancers [57].…”
Section: Alcohol Consumptionmentioning
confidence: 99%